Paul’s Conflicting Statements on Female Public Speaking (1 Cor. 11:5) and Silence (1 Cor. 14:34-35): A New Suggestion - Baum, Armin Daniel (Tyndale bulletin, 2014)
How could in 1 Corinthians women at the same time be permitted to prophesy (1 Cor. 11:5) and prohibited from asking questions (1 Cor. 14:34-35)? Read against their ancient cultural background the two texts reveal a common basic principle which lies behind both of them. According to Paul, female public speaking without male consent was unacceptable (1 Cor. 14:34-35) whereas female public speaking with male consent was tolerable if female chastity was preserved (1 Cor. 11:5).